Update on Transplacental Transfer of IgG Subclasses: Impact of Maternal and Fetal Factors - Clements, Toby; Rice, Thomas F.; Vamvakas, George; Barnett, Sara; Barnes, Megan; Donaldson, Beverly; Jones, Christine E.; Kampmann, Beate; Holder, Beth (Frontiers in Immunology, 2020)
Trans-placental antibody transfer from mother to fetus provides protection from infection in the first weeks of life, and the four different subclasses of IgG (IgG1, IgG2, IgG3, IgG4) have diverse roles in protection against infection. In this study, we evaluated concentrations and trans-placental transfer ratios of the IgG subclasses in a healthy UK-based cohort of mother-cord pairs, and investigated associations with maternal, obstetric, and fetal factors. In agreement with previous studies, we found a strong association between maternal and cord IgG for all subclasses. We report a transfer efficiency hierarchy of IgG1>IgG3>IgG4=IgG2 in our study population, and our review of the literature demonstrates that there is no consensus in the hierarchy of subclass transfer, despite the commonly made statement that the order is IgG1>IgG4>IgG3>IgG2. We report additional data regarding negative associations between elevated maternal IgG concentrations and maternal/cord transfer ratios, finding an effect on IgG1, IgG2 and IgG3 subclasses. Levels of IgG subclasses were the same between venous and arterial blood samples from the umbilical cord, but there was a significantly higher level of total IgG in arterial blood. We found no correlation between placental FcRn protein levels and IgG transfer in our cohort, suggesting that IgG is the main determinant of observed differences in trans-placental transfer ratios at term. Neonatal IgG1 and IgG4 levels were increased with later gestation at delivery, independent of any increase in trans-placental transfer, indicating that the benefit of later gestation is through accumulation of these subclasses in the fetus. Neonatal IgG2 levels and transfer ratios were reduced in rhesus-negative pregnancies, suggesting that administered anti-D antibodies may compete for trans-placental transfer of this subclass. Maternal influenza vaccination resulted in elevated transfer and neonatal levels of IgG4, whereas maternal Tdap vaccination had no impact on neonatal levels of the subclasses, nor transfer. However, within Tdap vaccinated pregnancies, later gestation at Tdap vaccination was associated with higher trans-placental transfer. Our study provides information regarding levels and transfer of IgG subclasses in healthy term pregnancies and demonstrates the importance of recording detailed clinical information in studies of antibody transfer, including parity, ethnicity, and timing of maternal vaccine delivery.